Introdução à pesquisa com sequências didáticas na formação continuada online de professores de ciências - Massi, Luciana; Giordan, Marcelo (Faculdade de Educação da Universidade Federal de Minas Gerais, 2014)
The integration of research in teaching practices assumes increasing importance and complexity in education. One aspect involved in this issue and poorly investigated is the training of teachers for the development of research linked with their practices. In this context, we present a training for research developed on a distance-learning course in the Science Teaching, which involves the design, implementation and analysis of didactic sequences: the Study Guide to the Initiation of the Term Paper (SGITP). Our research goal is to present a training proposal produced from the results collected from a survey of the literature of the area, and to investigate its application and its results in the teachers' continuing education program. Using data extracted from the production of students and tutors, we concluded that SGITP had a good acceptance among them and it was positively evaluated by teachers, in addition to promoting a greater understanding of research.

A inserção da pesquisa na prática docente assume cada vez maior importância e complexidade no campo da educação. Um aspecto envolvido na questão e pouco investigado é a formação dos professores para o desenvolvimento de pesquisas articuladas à sua prática. Nesse contexto, apresentamos uma proposta de formação para a pesquisa desenvolvida em um curso a distância de especialização em Ensino de Ciências envolvendo a elaboração, aplicação e análise de sequências didáticas: o Estudo Dirigido de Iniciação ao Trabalho de Conclusão de Curso (EDITCC). O objetivo do trabalho é apresentar a proposta formativa, produzida a partir dos resultados de pesquisa recolhidos da literatura da área, e investigar sua aplicação e seus resultados na formação continuada de professores de Ciências. Por meio de dados extraídos da produção de cursistas e tutores, percebemos que o EDITCC teve boa aceitação, foi positivamente avaliado pelos professores, além de ter promovido um maior entendimento sobre pesquisa.
INTRODUCTION TO RESEARCH WITH DIDACTIC SEQUENCES IN ON LINE CONTINUOUS EDUCATION FOR SCIENCE TEACHERS
Keywords: Continuing Education of Researchers and Teachers; Term Paper; Science Teaching; Introduction to Research.; Formação de pesquisadores e professores; Trabalho de conclusão de curso; Ensino de Ciências; Introdução a pesquisa.